Treatment of Patients with Acute Coronary Syndrome with ST Segment Elevation in Clinical Practice of the Republic of Karelia: the Results of 10-year Register - I. S. Skopets; N. N. Vezikova; A. V. Malafeev; A. N. Malygin; V. A. Litvinova (Рациональная фармакотерапия в кардиологии)
Aim. To study the clinical course, treatment, and outcomes in the patients with ST segment elevation acute coronary syndrome (STeACS) in real clinical practiceMaterial and methods. Our study is based on data of 5694 patients who were sequentially hospitalized in the Regional Vascular Center from 01.01.2009 to 01.01.2019 due to STeACS and included in the Federal Hospital Register. Men prevailed (65.8%); the average age was 68 years old. 14.1% of the patients had the history of myocardial infarction (MI) before this hospitalization. The reperfusion strategy, drug therapy, as well as the risks of complications and outcomes in real clinical practice of the Republic of Karelia were analyzed. Descriptive statistics methods were used to evaluate the results.Results. In the study group a high frequency of reperfusion interventions (83.5%) with a predominance of percutaneous coronary intervention (PCI; 76.2%) was revealed, as well as optimal drug therapy in most patients. Thus, 99.4% of patients took aspirin, 82.8% – clopidogrel, 91.1% – anticoagulants, 91.6% – beta-blockers, 95.6% – statins, 94.2% – angiotensin-converting-enzyme inhibitors/angiotensin II receptors blockers. A risk assessment of hospital and 6-month mortality was performed using GRACE score. The distribution of the hospital risk mortality were the following: 25.7% of patients had a low (49-125 points), 33.7% an average (126-154 points), and 40.6% of patients had a high risk (more than 154 points). At the same time, the risk of 6-month mortality in a half of the patients (51.6%) was low (27-99 points), the average risk (100-127 points) was determined in 23.0% of patients and the high risk (more than 127 points) – in 25.5% of patients. Life threatening complications developed in 38.1% of patients and the most frequent ones were arrhythmias (31.5%). The outcomes at the discharge from the hospital were as follows: 1432 patients (63.5%) had Q MI, 390 (17.3%) – non Q MI, 76 (3.4%) – unstable angina, 21 (0.9%) – MI of unspecified localization and 317 patients (14.1%) – repeated myocardial infarction.Conclusion. According to the results of a 10-year hospital registry of patients with STeACS, a high frequency of reperfusion interventions and an optimal drug therapy in most patients was revealed. However, to increase the effectiveness of treatment, it is necessary to minimize temporary losses both at the prehospital treatment and during reperfusion.